MANAJEMEN MALAM BINA IMAN DAN TAQWA UNTUK PENGUATAN KARAKTER PESERTA DIDIK - Riski Ariska Widiana; Agus Timan (Universitas Negeri Malang, 2019)
Abstract: The purpose of this studied was to describe the management of Malam Bina Iman dan Taqwa (Mabit) to strengthen the character of students. Study used a qualitative approached. Data collection used interview, observation, and documentation. Conclusions from this studied were (1) planning based on the goals of the madrasa, indicators of the success of attendance and discipline of students, determination of material, budget, location, (2) division of task and responsibilities of each committee, (3) inter-teacher briefings, briefings on students, implementation of special and general materials, (4) evaluations carried out every month and semester in the form of oral reports and attendance lists of students, (5) there were several factors that affect their management, including parents, teachers, environment, facilities and infrastructure, weather. Keywords: management of malam bina iman dan taqwa, character strengthening Abstrak: Tujuan penelitian ini untuk mendeskripsikan manajemen Malam Bina Iman dan Taqwa (Mabit) untuk penguatan karakter peserta didik. Penelitian menggunakan pendekatan kualitatif. Pengumpulan data menggunakan metode wawancara, observasi, dan dokumentasi. Simpulan dari penelitian ini adalah (1) perencanaan berdasarkan tujuan madrasah, indikator keberhasilan kehadiran dan kedisiplinan peserta didik, penentuan materi, anggaran, lokasi, (2) pembagian tugas dan tanggung jawab setiap panitia, (3) briefing antar guru, briefing terhadap peserta didik, pelaksanaan materi khusus dan umum, (4) evaluasi yang dilakukan setiap bulan dan semester dalam bentuk laporan secara lisan dan daftar kehadiran peserta didik, (5) terdapat beberapa faktor yang mempengaruhi manajemennya, antara lain orang tua, guru, lingkungan, sarana dan prasarana, cuaca. Kata Kunci: manajemen malam bina iman dan taqwa, penguatan karakter